A Fuzzy ^- ideal of aBH- algebra - Karrar Deiaa Mohamed (Journal of Kufa for Mathematics and Computer, 2017)
In this paper, we introduce the notions of - ideal of a ℬℋ-algebra in ordinary and fuzzy senses. Also, we give some properties of them and link these notions with some types of ideals of ℬℋ- algebra in ordinary and fuzzy senses .The image and preimage of fuzzy - ideal under a ℬℋ homomorphism are investigated